2019
DOI: 10.5897/jaerd2018.0999
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of social media mainstreaming in E-extension by agricultural development programmes in North Central Zone, Nigeria

Abstract: Social media is a new trend in communication and a new platform for sharing, engagement and networking in all spheres of life including agriculture. This study analysed social media mainstreaming in e-extension services delivery by the Agricultural Development Programmes (ADPs) in North CentralZone of Nigeria. Four ADPs of Kogi, Federal Capital Territory, Nasarawa and Niger states that participated in the Research Extension Farmer Input Linkage (REFIL) activities in November 2017 were purposively selected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In an attempt to enhance and ensure attainment of developed agriculture in the country were integration of support services such as Agricultural Development Programs (ADP) and River-Basin Development Authority (RBDA) nationwide. The ADP, developed in 1975, was adopted to provide extension service delivery to the farmers, drawing innovative and technical information from the research outputs to guide the farmers on technicalities of farm practices [39,40]. In view of this, a network of research-extension-farmer-input linkage systems was put in place to ensure that research; extension, and input service delivery are readily available to the farmers for improved productivity.…”
Section: Agricultural Support Servicementioning
confidence: 99%
“…In an attempt to enhance and ensure attainment of developed agriculture in the country were integration of support services such as Agricultural Development Programs (ADP) and River-Basin Development Authority (RBDA) nationwide. The ADP, developed in 1975, was adopted to provide extension service delivery to the farmers, drawing innovative and technical information from the research outputs to guide the farmers on technicalities of farm practices [39,40]. In view of this, a network of research-extension-farmer-input linkage systems was put in place to ensure that research; extension, and input service delivery are readily available to the farmers for improved productivity.…”
Section: Agricultural Support Servicementioning
confidence: 99%
“…This situation is not uncommon in many countries. For example, India and Nigeria are also faced with similar constraints ( Bhattacharyya et al, 2018;Ifejika et al, 2019). Asides from this, many other issues associated with the F2FEM include untimely dissemination of information, geographical distances, poor roads and transportation services, and lack of proper communication infrastructure (Abdullahi, Shehu & Sani, 2016;Sani et al, 2018).…”
Section: The Need For South Africa To Adopt Alternative Media Usagementioning
confidence: 99%
“…The social media used mainly by the respondents have a rich share of visual display in communication. Ifejika, Asadu, Enibe, Ifejika, &Sule, (2019) pointed out that as at July 2017 the global social media login users was 2 billion people for Facebook, 1.5 billion for Youtube and 1.2 billion for Whatsapp and Facebook messenger. Twitter recorded 328 million monthly users in the globe, the authors pointed out; however, the use of Twitter by the respondents was more, as indicated by the data.…”
Section: Model Specificationmentioning
confidence: 99%
“…Social media provides the platform for effective agricultural information dissemination, communicating measures and practices and to utilize opportunities, address challenges facing agricultural sector in developing countries. Social media is important in the dissemination and creation of awareness on agricultural technologies and development knowledge in real time (Ifejika, Asadu, Enibe, Ifejika & Sule, 2019). However, reaching farmers with only traditional extension system is a big challenge and may continue to prove abortive considering the barriers to effective agricultural extension in developing countries which seeks to create opportunities to connect more farm families with extension agents.…”
Section: Introductionmentioning
confidence: 99%